Angiogenic factors are elevated in overweight and obese individuals - Silha, J.V; Kršek, Michal; Sucharda, Petr; Murphy, L.J (International journal of obesity, 2005)
BACKGROUND: Adipose tissue produces both vascular growth factors and inhibitors. Since obesity is associated with expansion of the capillary bed in regional adipose depots the balance between these factors may favor angiogenesis. OBJECTIVE: To investigate the relationship between body mass index and serum concentrations of vascular growth factors in human subjects. METHODS: Vascular endothelial growth factor (VEGF), VEGF-C, VEGF-D, soluble VEGF receptor-2 (sVEGFr2), hepatocyte growth factor (HGF), angiopoietin-2, angiogenin and endostatin concentrations were measured in serum collected from 58 lean (24 males, 34 female, mean BMI, 22.2+/-0.3) and 42 overweight and obese (16 males and 26 females, mean BMI, 33.5+/-1.2) subjects after an overnight fast. RESULTS: Sexual dimorphism was apparent in the serum concentrations of VEGF-C, VEFG-D and angiopoietin-2 with significantly higher levels in female compared to male subject. VEGF, VEGF-C, VEGF-D, soluble VEGF receptor-2, angiopoietin-2, angiogenin and endostatin but not HGF were significantly elevated in overweight and obese subjects. Positive correlations between BMI and the serum concentrations of VEGF-C, VEGF-D, sVEGF-R2, angiopoietin-2, angiogenin and endostatin were observed even after adjustment for gender and age. CONCLUSIONS: Increased levels of vascular growth factors as well as the angiogenesis inhibitor endostatin are present in overweight and obese subjects and may contribute to previously documented increased risk of metastatic disease in obese subjects with cancer.
Keywords: Adult; dospělí; vaskulární endoteliální růstový faktor D; receptor 2 pro vaskulární endoteliální růstový faktor; obezita; Insulin Resistance; Sex Characteristics; Vascular Endothelial Growth Factor D; Humans; mužské pohlaví; Middle Aged; adiponektin; endostatiny; angiopoetin-2; pankreatická ribonukleasa; Overweight; Vascular Endothelial Growth Factor Receptor-2; leptin; angiogenní proteiny; Female; Hepatocyte Growth Factor; vaskulární endoteliální růstový faktor C; vaskulární endoteliální růstový faktor A; Male; Vascular Endothelial Growth Factor C; Angiogenic Proteins; Ribonuclease, Pancreatic; pohlavní dimorfismus; Endostatins; lidé středního věku; nadváha; lineární modely; Adiponectin; ženské pohlaví; analýza rozptylu; hepatocytární růstový faktor; Angiopoietin-2; Leptin; inzulinová rezistence; Obesity; lidé; Linear Models; Analysis of Variance; Vascular Endothelial Growth Factor A